Persepsi Siswa Terhadap Penerapan E-LKPD Neraca Lajur di SMK Bina Jaya Palembang - Ambalika, Reza; Januardi, Januardi; Lestari, Neta Dian (Journal of Innovation in Teaching and Instructional Media, 2024)
The purpose of this study was to see how students view the implementation of E-LKPD (Electronic Student Worksheet) on the Trial Balance material at SMK Bina Jaya Palembang. To measure the aspects of ease of use, effectiveness, and attractiveness of E-LKPD, this study used a quantitative descriptive method. The results showed that students were very positive about the use of E-LKPD, especially regarding the ease of navigation and interaction. With interactive features and direct feedback, E-LKPD is also considered to help students understand the Trial Balance concept independently. The visual appeal of E-LKPD also increases students' desire to learn. The results show that E-LKPD is an effective and appropriate learning method to support accounting learning in SMK, especially topics that require procedural understanding.